Produktivitas Kerja Karyawan Bagian Pelayanan di Kabupaten Kudus ditinjau dari Analisis Peran Stres Kerja dan Komunikasi - Olivia Winarti; Rr. Dwi Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to empirically determine work stress and communication on the work productivity of service employees in Kudus Regency. The participants involved were 174 service employees using purposive sampling. The measuring instruments used to obtain data are the work productivity scale, work stress scale and communication scale. The results of the major hypothesis test show that there is a very significant positive relationship between work stress and communication on work productivity in Kudus Regency service employees (significance 0.000 (p<0.1); the correlation coefficient for the three variables is 0.628; with an effective contribution of the major hypothesis of 39.4%). The results of the minor hypothesis test on the work stress variable and work productivity of service department employees in Kudus Regency show that there is a very significant positive relationship between the two, (significance 0.000 (p<0.05); correlation analysis between the two variables is 0.499. These results are the same as the results of the minor hypothesis on the communication variable with work productivity of service department employees in Kudus Regency (significance 0.000 (p<0.05); the correlation between the two variables is 0.407. This research concludes that work stress and Communication is influential and has a positive and significant relationship with the work productivity of service employees in Kudus Regency.